EFFICIENCY OF DISINFECTION OF GRAIN CROP SEED IN ZABAIKALYE - M. D. Dabaeva; N. B. Mardvaev (Зерновое хозяйство России, 2018)
Unfavourable phyto sanitary situation in the republic of Buryatia, connected with a growth of infected grain crops, including rots, needs study of seed disinfectors. Eight varieties of spring wheat zoned in Buryatia have been studied. According to the laboratory experiments the share of infected sprout on the control variants was above admissible harmfulness (from 17 to 36%). After disinfection with ‘Tebu-60’, ME and ‘Skarlet’, ME the level of seed infection with phyto pathogens decreased to 2-8%. However, the treatment with the disinfectors suppressed the development of coleoptile and roots. The experiments showed the difference of physiological response of spring wheat varieties on drugs. The article has presented the study results of the influence of disinfection with ‘Tebu-60’ and ‘Skarlet’ on the seed infection, germination and development of germinal organs of five varieties of barley. The seed infection significantly decreased after disinfection, especially after the use of ‘Tebu-60’. The disinfector ‘Tebu-60’ showed the strongest phyto toxic property and ‘Skarlet’ showed the weakest one. Biologic productivity of the spring wheat variety ‘Buryatskaya ostistaya’ was 2.42 t/ha without the application of disinfectors. The productivity of the grain crop after disinfection with ‘Tebu-60’, ME was the similar to the control. The drug ‘Skarlet’, ME increased wheat productivity on 0.41 t/ha. The wheat variety ‘Lyutestsens 937’ and the barley variety ‘Krasnoyarsky 80’ are the most resistant to phyto toxic effect of the disinfectors.